Performance Measurement And Management System a Inter Company Case Study Approach - Tamilnadu , India (Global Journal of Management and Business Research, 2014)
The field of performance measurement and management (PMM) is well filled with frameworks, models and guidelines addressing what to measure and how to design a performance measurement system (PMS). However, what has been less examined so far is how to ensure that PM Evolve in tandem with their environments. Further, the few approaches available today are prescriptive and outlines how or what practitioners should do in order to manage change in their PM
Keywords: performance measurement; performance measurement systems; performance management